The analysis of the lifestyle-related risk factors with an impact on human health in Romania - Cristian George Popescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
There's no doubt that the risk factors typical of a certain lifestyle which may have a negative impact on human health are numerous, especially considering that research in health (medicine, pharmacology etc) were focused on their determination, but especially on the cause-effect relationship. On the other hand, it's well known that people run a high economic risk when they don't invest in actions aiming to prevent certain diseases, especially when the disease risk grows. According to specialized studies, about 30% of all modern autoimmune diseases, among which there is cancer, are due to the eating habits. Considering that there are several risk factors, we realize the importance of studying the food factor, especially from the point of view of statistic research regarding food consumption in Romania and it's important to point out the dangers hiding behind these foods. The most important ones are: water and air, refreshments, meat and meat products, sugar, cigarettes and alcohol.
Keywords: 330; lifestyle; risk factors; habitats; pollution; food pollution